Effectiveness of State Administrative Law: Perspectives Comparative from Indonesia and Singapore in Public service - Syafa'i, Imam; Megasari, Indah Dewi (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Study This aiming for analyze and compare the effectiveness of State Administrative Law (HAN) in Indonesia and Singapore in context service public. Through approach comparative, research This make an effort identify similarities and differences in structure, system , implementation , and effectiveness of HAN in both countries. The methodology used is approach qualitative with studies case, collecting data through studies documents, analysis regulation legislation, as well as literature related . Research results show that although there is difference in approaches and priorities policy, both countries have the same goal, namely increase quality service public . In Indonesia, the challenges main lies in the implementation regulations and enforcement consistent law, while in Singapore, the focus more on efficiency and innovation technology in service public. Comparison This give outlook valuable about practice best and areas that need improved in each country. Research This conclude that HAN effectiveness is highly context dependent social , cultural and political a country, and commitment government towards bureaucratic reform and improvement service public